Design of the New Flex Wheel Tooth Profile for Harmonic Drive Based on Transient Dynamics - Zheng Junjian; He Xueming; Li Pengchao (Jixie chuandong)
In order to improve the transmission performance and meshing performance of harmonic gear drives, a new type of flexible gear tooth profile is designed on the basis of the comparison of the meshing backlash of different tooth profiles by analyzing the movement tracks of different tooth profiles. The new type of flexible gear tooth profile is obtained by fitting the tooth profile segment with the minimum meshing backlash, mainly combining the meshing backlash comparison of S-type flexible gear tooth profile, common tangent double circular arc flexible gear tooth profile and double circular arc flexible gear tooth profile. The contact model of the harmonic gear drive is established through Ansys Workbench, and the deformation characteristics of flexsplines are analyzed using transient analysis method; through the transient analysis results of different tooth profiles under no-load and loading conditions, it is verified that the meshing performance of the new type of tooth profile is superior.